2017
DOI: 10.1063/1.4993612
|View full text |Cite
|
Sign up to set email alerts
|

Over-injection and self-oscillations in an electron vacuum diode

Abstract: We demonstrate a practical means by which one can inject more than the space-charge limiting current into a vacuum diode. This over-injection causes self-oscillations of the space-charge resulting in an electron beam current modulation at a fixed frequency, a reaction of the system to the Coulomb repulsive forces due to charge accumulation. Published by AIP Publishing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The behavior described so far is similar to that presented in Ref. 10, apart from the period of the oscillations and the values of the currents and voltages because of the different conditions resulting from the cathode shape, dimensions, the voltage rise time, and electron collisions with the grids.…”
Section: Pic Simulations Of the Electron Dynamics In The Experimesupporting
confidence: 81%
See 4 more Smart Citations
“…The behavior described so far is similar to that presented in Ref. 10, apart from the period of the oscillations and the values of the currents and voltages because of the different conditions resulting from the cathode shape, dimensions, the voltage rise time, and electron collisions with the grids.…”
Section: Pic Simulations Of the Electron Dynamics In The Experimesupporting
confidence: 81%
“…We have experimentally demonstrated that our scheme proposed in Ref. 10 to produce a modulated electron beam by over-injecting a diode is feasible, but we have not been able to reproduce the periodic behavior with the expected frequency because our dispenser cathode did not emit uniformly over its entire surface. By PIC simulations, we have shown the complications introduced by having a finite area cathode, scattering from finite transmission grids, and the voltage applied on the cathode rising during a finite time.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations